Educational Play Snakes and Stairs Can Overcome Anxiety in Children's Hospitalization - Padila, Padila; Andri, Juli; Andrianto, Muhammad Bagus; Sartika, Andry; Oktaviyani, Yesi (JOSING: Journal of Nursing and Health, 2022)
This study aims to determine the effect of snake and ladder educational game therapy (APE) on reducing anxiety in hospitalized children. This study uses an experimental method with a one-group pre-post test design. The number of samples used in this study was 15 samples with an incidental sampling technique. The results showed that the average level of anxiety before playing snake and ladder therapy in treated children was 19.13 with the moderate anxiety category. The anxiety story after snake therapy in treated children was 14.20 with mild class. In conclusion, playing snake and ladder therapy reduces anxiety in hospitalized children. Keywords: Educational Game (APE), Snake and Ladder, Decreased Anxiety Level of Children (Pre-School)